Studying The Driving Factors Of CO2 Emissions Under The Environmental Kuznets Curve Using The STIRPAT Model: The Case Of Syria (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Energy is the artery that feeds the economic sectors, and the nerve that no country can achieve economic growth rates without it, but it is the main cause of climate change due to greenhouse gas emissions, the most important of which is CO2, as a result, it was necessary to research the basic factors of CO2 emissions in Syria, in order to know the nature of the relationship between economic growth environmental degradation represented by CO2 emissions, using the STIRPAT methodology that relies on the Partial Least Squares (PLS) method. The study found that economic growth is the first main factor for CO2 emissions in Syria, followed by energy consumption, then population growth and the percentage of urbanization in the last and second to last place respectively, but carbon dioxide emissions and economic growth are growing steadily in Syria, thus the absence of the Environmental  Kuznets Curve, which confirms the need to pay attention to environmental policies and move towards using renewable energy to reduce the environmental pollution in Syria